Changing Lives in Laos: Society, Politics, and Culture in a Post-Socialist State - Santamaria, Matthew (Kasarinlan: Philippine Journal of Third World Studies; Vol 32 No 1,2 (2017): TWSC and Forty Years of Critical Scholarship, 2018)
Review of Changing Lives in Laos: Society, Politics, and Culture in a Post-Socialist State , edited by Vanina Bouté and and Vatthana Pholsena.